2020
DOI: 10.1111/acel.13159
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training reverses cardiac aging phenotypes associated with heart failure with preserved ejection fraction in male mice

Abstract: Heart failure with preserved ejection fraction (HFpEF) is the most common type of HF in older adults. Although no pharmacological therapy has yet improved survival in HFpEF, exercise training (ExT) has emerged as the most effective intervention to improving functional outcomes in this age‐related disease. The molecular mechanisms by which ExT induces its beneficial effects in HFpEF, however, remain largely unknown. Given the strong association between aging and HFpEF, we hypothesized that ExT might reverse car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(79 citation statements)
references
References 46 publications
6
73
0
Order By: Relevance
“…Furthermore, the common biological processes among the three tissues were mainly related to cell cycle and immune response. These findings were consistent with those of previous studies, which demonstrated that cell cycle and immune response are closely related to diastolic dysfunction and impaired cardiac reserves ( Roh et al, 2020 ; Sava et al, 2020 ). Heart function is related to the flow dynamics of the cerebral artery, which may influence the gene expression in the cerebral artery and increase the incidence of cerebrovascular events ( Karahan et al, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the common biological processes among the three tissues were mainly related to cell cycle and immune response. These findings were consistent with those of previous studies, which demonstrated that cell cycle and immune response are closely related to diastolic dysfunction and impaired cardiac reserves ( Roh et al, 2020 ; Sava et al, 2020 ). Heart function is related to the flow dynamics of the cerebral artery, which may influence the gene expression in the cerebral artery and increase the incidence of cerebrovascular events ( Karahan et al, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…The reasons for this are unclear but might reflect reduced ability of the heart to undergo physiological hypertrophy due to a more advanced age (~ 5.5 months of age). This is in line with studies reporting lack of exercise-induced hypertrophy in aged animals 45 , 46 . In contrast, our data suggest that GDM is associated with concentric remodeling/hypertrophy, both at term and postpartum, as HIP females showed increased diastolic thickness of both interventricular septum (Fig.…”
Section: Discussionsupporting
confidence: 92%
“… 170 At an age of 24–30 months, mice recapitulate many hallmarks of human HFpEF pathophysiology, including diastolic dysfunction, concentric hypertrophy with fibrosis and reduced exercise capacity. 171 , 172 This mice furthermore have lung congestion and increased natriuretic peptide levels. Hypertension or T2DM, however, have not been described.…”
Section: Validation and Translation Of The H2fpef And Hfa-peff Scores In Animal Modelsmentioning
confidence: 95%